Truncating mutations of MAGEL2 cause Prader-Willi phenotypes and autism - Schaaf, Christian P; Gonzalez-Garay, Manuel L; Xia, Fan; Potocki, Lorraine; Gripp, Karen W; Zhang, Baili; Peters, Brock A; McElwain, Mark A; Drmanac, Radoje; Beaudet, Arthur L; Caskey, C Thomas; Yang, Yaping (Nature genetics, 2013)
Christian Schaaf, Manuel Gonzalez-Garay and colleagues report the identification of four individuals with truncating mutations on the paternal allele of MAGEL2 , a gene within the imprinted domain linked to Prader-Willi syndrome (PWS). The four individuals have PWS or PWS-related phenotypes, and all have autism. Prader-Willi syndrome (PWS) is caused by the absence of paternally expressed, maternally silenced genes at 15q11-q13. We report four individuals with truncating mutations on the paternal allele of MAGEL2 , a gene within the PWS domain. The first subject was ascertained by whole-genome sequencing analysis for PWS features. Three additional subjects were identified by reviewing the results of exome sequencing of 1,248 cases in a clinical laboratory. All four subjects had autism spectrum disorder (ASD), intellectual disability and a varying degree of clinical and behavioral features of PWS. These findings suggest that MAGEL2 is a new gene causing complex ASD and that MAGEL2 loss of function can contribute to several aspects of the PWS phenotype.